Efficient Colorimetric Fluoride Anion Chemosensors With Varied Colors Based on Simple Aminobenzodifuranone Organic Π-Conjugated Dyes - Deng, Zhi Feng; Li, Rui; Geng, Jie Ting; Zheng, Meng; Li, Lei Quan; Shi, Xin; Ren, Wen Qi; Meng, Zi Yue; Ji, Zhuo Ting; Hua, Jing (Frontiers in Chemistry, 2020)
High selectivity and sensitivity detection of fluoride anions (F−) in an organic solution by the naked eye has always been a challenge. In this investigation, a simple compound based on aminobenzodifuranone (ABDF) was designed and synthesized. Deprotonation of the amino moiety caused by F− is responsible for a color change from dark blue to various colors (colorless, yellow, orange, and red) in different common organic solvents due to a blue shift over 200 nm in the UV/Vis spectrum. The color change is quite visible to the naked eye under ambient light. The detection limit for F− can reach a concentration of as low as 5.0 × 10−7 M with high selectivity, even in a solution containing multiple anions.